Els «murtats» encara - Colón, Germà (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: A study about the atymology of murtat (guide, messenger) through text criticism. It appears in Ramon Muntaner’s Crònica, but its meaning has not been well interpreted by other etymologists.